Internal Quality Assurance Model for Small Schools - Natun, Jaruwan (Rajapark Journal, 2024)
This research aimed to 1) synthesize the results of external quality assessment of small schools, 2) construct an internal quality assurance model of small schools, and 3) examine and evaluate the usefulness of the internal quality assurance model of small schools. This research was qualitative. The samples used in the study were small schools in the development network of the Faculty of Education, Pibulsongkram Rajabhat University, academic year 2023, that voluntarily participated in the project, totaling 10 schools. The informants were 10 school administrators and 10 academic teachers, obtained by purposive size determination. There were 7 experts in the focus group. Tools used for data collection include 1) document synthesis record form 2) structured interview form, and 3) appropriateness check and usefulness evaluation form. The data were analyzed by content analysis. The research results found that 1) The internal quality assurance system in small schools consists of 1.1) determining policy and quality assurance standards; 1.2) personnel training and development; 1.3) context and needs analysis; 1.4) preparing development plans and operations; 1.5) monitoring and evaluation; and 1.6) preparing self-evaluation reports. 2) The internal quality assurance model in small schools consists of inputs, processes, products, outcomes, and impacts. 3) The usefulness of the internal quality assurance model in small schools is at a high level.